2D SnS2 Nanostructure-Derived Photocatalytic Degradation of Organic Pollutants Under Visible Light - Srivastava, Rohit Ranjan; Kumar Vishwakarma, Pramod; Yadav, Umakant; Rai, Suyash; Umrao, Sima; Giri, Rajiv; Saxena, Preeti Suman; Srivastava, Anchal (Frontiers in Nanotechnology, 2021)
Wastewater produced by the textile industry contains various dyes and organic compounds that directly or indirectly affect surface water or groundwater pollution. Visible-light-driven semiconductor photocatalysis is the leading pathway for the degradation of environmental pollutants. Herein, we report the bottom-up hydrothermal growth of 2D tin disulfide Nanostructures (SnS2 NSs) for efficient photodegradation of organic pollutants such as Rhodamine B (Rh.B) and Methyl Violet (M.V) in an aqueous medium under visible light (λ > 400 nm) irradiation. The as-synthesized SnS2 NSs were characterized by various structural, morphological, and optical techniques such as XRD, RAMAN, TEM, UV-Vis, BET, etc. Furthermore, the low bandgap (~1.6 eV), high surface area (56m2/g), and the anionic nature of SnS2 NSs attribute an efficient photocatalyst for photocatalytic applications. The photocatalytic properties of SnS2 NSs showed good degradation efficiency of 93% and 99.6% for Rh. B and M.V respectively in 25 minutes. The kinetic rate constant of these dyes was estimated by using the Langmuir-Hinshelwood model. Here, we also performed the recyclability test of photocatalyst and discussed the plausible mechanism for the photocatalytic degradation of organic pollutants. Moreover, In-vitro cytotoxicity was also evaluated against human cervical cancer cell lines (HeLa cells) with different concentrations (0-1000 μg/ml) of as-synthesized SnS2 NSs. This purposed work provides a possible treatment for the degradation of organic pollutants under visible light to balance the aquatic ecosystems.